1971
DOI: 10.1093/bja/43.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Two Comparisons of the Analgesic Activity of Orally Administered Pentazocine, Dihydrocodeine and Placebo

Abstract: Two double-blind between-patient comparisons of the analgesic activity of orally administered pentazocine 50 mg, dihydrocodeine 60 mg and placebo are described, which involved 99 patients in "severe" or "moderate" pain, mainly of skeletal origin, and 103 patients in "severe" or "moderate" pain predominantly of postoperative origin. In both studies pain was assessed by a single observer prior to and 1 hour after the administration of a single dose of one of the test preparations. Both active drugs were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A placebo was not included in either study because it was felt undesirable to use this for patients who were in moderate or severe pain. In addition, two of the earlier studies by Davie and Masson (1970) and Daniel, Wilkins and Nicholson (1971) had already demonstrated the efficacy of pentazocine as compared with a placebo. The nurse assessors had been trained in the use of the method in a previous study when pethidine was compared with a placebo to demonstrate the sensitivity of the technique of assessment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A placebo was not included in either study because it was felt undesirable to use this for patients who were in moderate or severe pain. In addition, two of the earlier studies by Davie and Masson (1970) and Daniel, Wilkins and Nicholson (1971) had already demonstrated the efficacy of pentazocine as compared with a placebo. The nurse assessors had been trained in the use of the method in a previous study when pethidine was compared with a placebo to demonstrate the sensitivity of the technique of assessment.…”
Section: Discussionmentioning
confidence: 98%
“…Pentazocine (Fortral) is being increasingly used as a potent analgesic and there have been a number of recent studies in which pentazocine 50 mg and 70 mg given by mouth has been shown to be superior to a placebo (Davie and Masson, 1970) and equivalent to pethidine 100 mg by mouth (John, 1970). Daniel, Wilkins and Nicholson (1971) found a trend in which oral pentazocine 50 mg was superior to oral dihydrocodeine 60 mg and both active drugs were superior to placebo, while Economou, Monson and Ward-McQuaid (1971) found that patients in moderate pain experienced better relief with pentazocine 75 mg than with the other benzomorphan derivative, phenazocine 5 mg.…”
mentioning
confidence: 99%
“…Daniel et al performed two comparative, single doses, doubleblind studies in which analgesia and adverse effects of pentazocine 50 mg, DHC 60 mg and placebo administered orally were compared [43]. In the first trial 99 patients were recruited with moderate to severe pain, mainly from skeletal origin followed orthopedic surgery.…”
Section: Comparative Dihydrocodeine Studies In Patients With Postopermentioning
confidence: 99%
“…Although pentazocine 75 mg was stated to be statistically significantly better than phenazocine, as evidenced by the percentage of patients with moderate pain who experienced complete relief after administration, there were too few patients with mild or severe initial pain to enable valid comparisons. A firm trend for oral pentazocine 50 mg to be more effective than oral dihydrocodeine 60 mg in patients with moderate to severe pain of skeletal origin or resulting from a variety of surgical procedures was reported by Daniel et al (1971). Both drugs were more effective than a placebo.…”
Section: Oraladministrationmentioning
confidence: 99%